Centrum Semiovale Perivascular Space and Amyloid Deposition in Spontaneous Intracerebral Hemorrhage. Issue 7 (20th April 2021) - Tsai, Hsin-Hsi; Pasi, Marco; Tsai, Li-Kai; Huang, Chi-Ching; Chen, Ya-Fang; Lee, Bo-Ching; Yen, Ruoh-Fang; Gurol, M. Edip; Jeng, Jiann-Shing
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We explored whether high-degree magnetic resonance imaging–visible perivascular spaces in centrum semiovale (CSO) are more prevalent in cerebral amyloid angiopathy (CAA) than hypertensive small vessel disease and their relationship to brain amyloid retention in patients with primary intracerebral hemorrhage (ICH). Methods: One hundred and eight spontaneous ICH patients who underwent magnetic resonance imaging and Pittsburgh compound B were enrolled. Topography and severity of enlarged perivascular spaces were compared between CAA-related ICH (CAA-ICH) and hypertensive small vessel disease–related ICH (non-CAA ICH). Clinical and image characteristics associated with high-degree perivascular spaces were evaluated in univariate and multivariable analyses. Univariate and multivariable models were performed to evaluate associations between the severity of perivascular spaces in CSO and amyloid retention in CAA-ICH and non–CAA-ICH cases. Results: Patients with CAA-ICH (n=29) and non–CAA-ICH (n=79) had similar prevalence of high-degree perivascular spaces in CSO (44.8% versus 36.7%; P =0.507) and in basal ganglia (34.5% versus 51.9%; P =0.131). High-degree perivascular spaces in CSO were independently associated with the presence of lobar microbleed (odds ratio, 3.0 [95% CI, 1.1–8.0]; P =0.032). The amyloid retention was higher in those with high-degree than those with low-degree CSO-perivascular spaces in CAA-ICH (global Pittsburgh compound B standardized uptake value ratio, 1.55 [1.33–1.61] versus 1.13 [1.01–1.48]; P =0.003) but not in non–CAA-ICH. In CAA-ICH, the association between cerebral amyloid retention and the degree of perivascular spaces in CSO remained significant after adjustment for age and lobar microbleed number ( P =0.004). Conclusions: Although high-degree magnetic resonance imaging–visible perivascular spaces are equally prevalent between CAA-ICH and non–CAA-ICH in the Asian cohort, the severity of magnetic resonance imaging–visible CSO-perivascular spaces may be an indicator of higher brain amyloid deposition in patients with CAA-ICH.